2016
DOI: 10.2147/ott.s114389
|View full text |Cite
|
Sign up to set email alerts
|

The accumulation of macrophages attenuates the effect of recombinant human endostatin on lung cancer

Abstract: BackgroundAlthough anti-angiogenic therapy is widely applied clinically, its efficacy has been less than expected. Screening for regulatory factors and sensitive indicators to define the effectiveness of these drugs is required. Through a retrospective study of clinical data, we found that patients with a higher peripheral monocyte-to-lymphocyte ratio (MLR) obtained less benefit from recombinant human endostatin (rhES, Endostar®), an anti-angiogenic drug, in lung cancer. Because MLR is positively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In Eng-IKO e mice, the phenomenon of initial inhibition followed by rebound of tumour growth was observed. The present study indicated that increased infiltration of CD206-positive M2 macrophages and that this increased infiltration might lead to failure of antiangiogenic therapy (33). Moreover, we found that the increased number of infiltrated M2 macrophages might be due to activation of the IL-6/JAK2/STAT3 signalling pathway in the tumour microenvironment.…”
Section: Discussionsupporting
confidence: 54%
“…In Eng-IKO e mice, the phenomenon of initial inhibition followed by rebound of tumour growth was observed. The present study indicated that increased infiltration of CD206-positive M2 macrophages and that this increased infiltration might lead to failure of antiangiogenic therapy (33). Moreover, we found that the increased number of infiltrated M2 macrophages might be due to activation of the IL-6/JAK2/STAT3 signalling pathway in the tumour microenvironment.…”
Section: Discussionsupporting
confidence: 54%
“…In LLC xenograft mice, endostatin inhibited tumor angiogenesis by reducing the number of CD31+ cells and VEGF expression, aggravated hypoxia, and increased levels of inflammatory cytokines (IL-4, IL-6, IL-10) in tumor and CCL2 expression in endothelial cells and fibroblasts [224]. Contradictory to above listed examples, the percentage of F4/80+ macrophages was increased significantly after the treatment with recombinant human endostatin [224].…”
Section: The Effect Of Direct Inhibitors On Tam Amount and Repolariza...mentioning
confidence: 92%
“…In LLC xenograft mice, endostatin inhibited tumor angiogenesis by reducing the number of CD31+ cells and VEGF expression, aggravated hypoxia, and increased levels of inflammatory cytokines (IL-4, IL-6, IL-10) in tumor and CCL2 expression in endothelial cells and fibroblasts [224]. Contradictory to above listed examples, the percentage of F4/80+ macrophages was increased significantly after the treatment with recombinant human endostatin [224]. In patients with lung cancer treated with chemotherapy plus endostatin, a higher peripheral monocyte-to-lymphocyte ratio (MLR) was detected in patients who did not respond to the treatment (progressive disease) compared to the patients with partial regression [224].…”
Section: The Effect Of Direct Inhibitors On Tam Amount and Repolariza...mentioning
confidence: 99%
“…Chronic hypoxia has been reported to decrease the expression of this chemokine in glioma cells [154,155], HUVEC [156], monocytes and macrophages [144,157,158], and in uveal melanoma [159]. In contrast, it has also been reported to increase in breast cancer cells [142], cervical squamous carcinoma cells [46], hepatoma cells [160], in another study on HUVEC [161], dermal fibroblasts [162], Lewis lung carcinoma cells [163,164], multiple myeloma [165], primary mouse astrocytes [166], and vascular endothelial cells [167,168]. These discrepancies are associated with the complex regulation of expression of this chemokine in hypoxia.…”
Section: Impact Of Hypoxia On Ccr1 Expressionmentioning
confidence: 97%